Community connections post-pandemic: Socioeducational experience in Guacimo, Limón during the year 2022 - Salazar Vargas, Floribeth (2023)
Introduction: This article revisits the experience of workshops course: Local Organization and Community Building, based on the experience of establishing connections after the Covid-19 pandemic. It reconnects with the initial contacts for approach local spaces, the sensory-thinking learning experiences that students and the role of teachers in nurturing the web of relationships in which one also participates. Objective: To propose a sensitive analysis of the construction of common bonds and meanings that emerge in local dynamics, involving students and teaching. Method: Recovery, analysis, and reflection on the lived experience in the community practice of the third grade, during the year 2022, through three relationships: local spaces and teachers, students and teachers, students, local spaces, and teachers. Results: The process of returning to in-person activities had different paces in this experience. This situation was due to the evident need to (re)build social ties, to once again observe, feel, and engage with the everyday life of local spaces, student communities, and formal learning spaces. Conclusions: Cultivating connections as a sensitive process and collective care leads to the possibility of experiencing comprehensive learning spaces that, in turn, foster meaningful learning for all parties involved, who collectively recognize themselves as creators of diverse and valuable knowledge.